P13.15 Pre-clinical trial of T601 oncolytic virus for high grade glima via intra-tumoral injection. (9th September 2021) - He, Z; Meng, Z; Liang, P; Xing, L; Zheng, X; Wang, G
Abstract: BACKGROUND: An effective therapeutic method still hasn't been devised for lethal high grade glioma. Thus, a method with high anti-tumoral efficiency, tumoral targeting, and acceptable side effect needs to be designed. Oncolytic virotherapy which can specifically lyse tumor cells via mass replication and deleting nucleotide metabolism related gene, like TK, required in viral replication and overexpressed in tumor cells, provides hope for patients. However, the virus only contained TK deletion is unable to show sufficient specificity of anti-tumoral response in tumor cells. Here, the adapted strain of vaccinia virus with high tumoral specificity due to TK and RR deletion and FUC1 insertion, named T601, is chosen in this project. In clinical application, intra-tumoral injection showed improved anti-tumoral efficiency and acceptable side effect. However, intra-tumoral viral injection in orthotropic glioma model is rare. In this project, various biosafety and antitumoral efficiency parameter would be tested for confirming the biosafety and reliability of intra-tumoral T601 viral injection for future clinical trials. MATERIAL AND METHODS: For measuring the IC50 of T601, 10 different amounts of virus was tested in vitro via calculating cell viability with CCK-8(cell counting kit-8). For measuring the further antitumoral response of FCU1, different concentration of the 5-FC was added into the medium with IC50 viral amount. To ensure the biosafety of T601, MTD (maximum tolerance dose) was measured. Based on the MTD result, for evaluating the anti-tumoral efficiency, 106 pfu, 105 pfu, 104 pfu of virus was intra-tumoral injected in orthotopic GBM bearing mice. Tumor size was measured once a week through in vivo bioimaging system. RESULTS: 0.022 MOI, the IC50 of T601, showed high cytotoxicity of T601. Moreover, the significantly decreased cell viability under the combined treatment of 5-FC and 0.22MOI T601 showed intact anti-tumoral function. In MTD assay, except for 107 group, no significant weight loss was found. However, in 107 pfu group, mean body weight decreased around 10% and animal fatality happened on day 9. According to the MTD result, certain amount of virus was intra-tumorally injected. In all treatment group, the tumor size was significantly shrined. At the same time, the survival rate of mice under viral treatment was significantly extended. CONCLUSION: In summary, T601 exhibited efficient anti-tumoral function and acceptable side effect. T601 treatment prolonged the survival period of GBM mice with acceptable neurotoxicity, demonstrating that T601 contains necessary criterial for intra-tumoral injection. Ultimately, this project provided basic reference information of dose for future clinical trial.